2020
DOI: 10.3390/jcm9020427
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis-Predicting Model Based on [18F]fluorodeoxyglucose PET Metabolic Parameters in Locally Advanced Cervical Cancer Patients Treated with Concurrent Chemoradiotherapy: Multi-Center Retrospective Study

Abstract: This study aimed to develop a prognosis-predicting model based on [18F]fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) and clinicopathologic factors in locally advanced cervical cancer patients treated with concurrent chemoradiotherapy (CCRT). The medical records of 270 locally advanced cervical cancer patients who were treated with CCRT were collected from three institutions and reviewed retrospectively. A nomogram was used for predicting 2-year disease-free survival (DFS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…Higher NLR on pretreatment 18 F-FDG PET/CT images was shown to be an independent prognostic factor for worse distant metastasis-free survival in locally advanced nasopharyngeal carcinoma [ 22 ]. Similarly to our previous research [ 9 , 16 ], we found in the current study that nSUV max was a powerful biomarker for predicting tumor recurrence and death and that NLR and LBR were significant prognostic factors. However, normalized nSUV max to the liver or blood pool did not demonstrate superiority over conventional nSUV max for predicting tumor recurrence or survival.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Higher NLR on pretreatment 18 F-FDG PET/CT images was shown to be an independent prognostic factor for worse distant metastasis-free survival in locally advanced nasopharyngeal carcinoma [ 22 ]. Similarly to our previous research [ 9 , 16 ], we found in the current study that nSUV max was a powerful biomarker for predicting tumor recurrence and death and that NLR and LBR were significant prognostic factors. However, normalized nSUV max to the liver or blood pool did not demonstrate superiority over conventional nSUV max for predicting tumor recurrence or survival.…”
Section: Discussionsupporting
confidence: 89%
“…The largest retrospective study of 287 patients with FIGO stages IA2 to IVB cervical cancer established the following three prognostic groups based on tSUV max with five-year OS rates: 95% for a tSUV max of 5.2 or less, 70% for a tSUV max between 5.2 and 13.3, and 44% for a tSUV max greater than 13.3 [6]. Moreover, in a recent multicenter retrospective study that enrolled 270 patients with locally advanced cervical cancer treated with CCRT, a tSUV max of 12 or greater was an independent prognostic biomarker for predicting tumor recurrence (HR: 2.14; 95% CI: 1.32-3.47; p = 0.002) and death (HR: 3.06; 95% CI: 1.46-6.44; p = 0.003) [16].…”
Section: Discussionmentioning
confidence: 99%
“…Nine articles on SUV max in tumor tissue were included in the study [ 11 , 12 , 14 , 15 , 16 , 17 , 18 , 21 , 23 ]. The combined HR for EFS with the highest SUV max was 1.938 (95% CI = 1.203–3.054, p = 0.004) ( Figure S1A ), which meant that the patients with a high SUV max measurement in tumor tissue had a higher risk of recurrence or progression than those with a low SUV max .…”
Section: Resultsmentioning
confidence: 99%
“…Five articles on nodal SUV max were included in the study [ 13 , 14 , 20 , 22 , 23 ]. Where there was a significant heterogeneity ( I 2 = 69.4%, p = 0.011), the random-effects model was applied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation